2020
DOI: 10.1098/rstb.2019.0409
|View full text |Cite
|
Sign up to set email alerts
|

Joint inhibition of mitochondrial complex IV and alternative oxidase by genetic or chemical means represses chloroplast transcription in Arabidopsis

Abstract: Changes in the functional state of mitochondria have profound effects on other cellular compartments. Genome-wide expression analysis of Arabidopsis rps10 mutants with an RNAi-silenced expression of mitoribosomal S10 protein has revealed extensive transcriptional reprogramming. A meta-analysis comparing expression datasets of 25 mitochondrial perturbations showed a high similarity of the aox1a:rpoTmp mutant , which is defective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Primers of MGE1, ATPd, ATPδ, ATPβ and sHSP23.6 were designed with Primer Premier 5 program. Primers of OM66, ANAC013, SOT12, AOX1a, AOX1b, AOX1c, UPOX1, NBD4, sHSP23.5 and ACT were previously described (Clifton et al , 2005; Geisler et al , 2012; Kerchev et al , 2014; Zhang et al , 2014; Wu et al , 2019; Adamowicz-Skrzypkowska et al , 2020). qRT-PCR was performed with 2 × RealStar Green Power Mixture (gene star) in a QuantStudio 3 Real-Time PCR System (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Primers of MGE1, ATPd, ATPδ, ATPβ and sHSP23.6 were designed with Primer Premier 5 program. Primers of OM66, ANAC013, SOT12, AOX1a, AOX1b, AOX1c, UPOX1, NBD4, sHSP23.5 and ACT were previously described (Clifton et al , 2005; Geisler et al , 2012; Kerchev et al , 2014; Zhang et al , 2014; Wu et al , 2019; Adamowicz-Skrzypkowska et al , 2020). qRT-PCR was performed with 2 × RealStar Green Power Mixture (gene star) in a QuantStudio 3 Real-Time PCR System (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial retrograde regulation was first reported in Saccharomyces cerevisiae in which it was shown that perturbed respiratory function activates a retrograde pathway that regulates gene expression and thereby alters cellular metabolism [61]. The AOX genes represent the pre-eminent example of this system in plants [29,36,37,41]. In A. thaliana, the transcription of AtAOX1a has been shown to be strongly negatively regulated by ABI4 [38], but to be inducible by latent transcriptional factors including NAC17 [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…AOX has also been shown to be regulated in a retrograde manner [30][31][32][33][34][35][36][37]. For instance, the transcription factor ABI4 acts as a repressor of AOX1a, which is depressed under rotenone treatment [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…ANAC017 loss-of-function mutants showed increased susceptibility when grown on UPR mt -inducing media, while ANAC017 overexpression lines were more resistant. Another study in this issue performed whole-genome transcriptome studies on knock-down lines of another Arabidopsis mitochondrial ribosomal protein, RPS10 [175], which is also interesting as a model for UPR mt in plants. Here, the ANAC017 regulon was strongly induced, and the analysis showed that the only common differentially regulated genes between doxycycline treatment, mrpl1 and rps10 mutants were well-known AA-induced ANAC017 target genes (e.g.…”
Section: Retrograde Signalling From Mitochondria In Autotrophsmentioning
confidence: 99%
“…ANAC017 loss-of-function mutants showed increased susceptibility when grown on UPR mt -inducing media, while ANAC017 overexpression lines were more resistant. Another study in this issue performed whole-genome transcriptome studies on knock-down lines of another Arabidopsis mitochondrial ribosomal protein, RPS10 [175], which is also interesting as a model for UPR mt in plants.…”
Section: Retrograde Signalling From Mitochondria In Autotrophsmentioning
confidence: 99%